**Finding an iterative formula**

Starter

Make x the subject of these formulae:

(a) 3x - 2 = y

(b) 3x - y = 2

(c) 3x - y = 2

(d) 3x - y = 2

Activity

Put the cards together to show the creation of the iterative formulae.

Rearranging to give an iterative formula

'Making x the subject'

x - 2x + 3 = 0

**L.O. - Use rearrangement to generate an iterative formula.**

2

2

3

Starter

Make x the subject of these formulae:

(a) 3x - 2 = y x =

(b) 3x - y = 2 x =

(c) 3x - y = 2 x =

(d) 3x - y = 2 x =

2

2

3

y + 2

3

y + 2

3

y + 2

3

y + 2

3

2

3

3

Rearranging to give an iterative formula

'Making x the subject'

x - 2x + 3 = 0

3

x = 2x - 3

x = 2x - 3 OR

x = 2x - 3 OR

x = 2x - 3

x

x

3

2

3

2x = x + 3

x = x + 3

2

3

3

Rearranging to give an iterative formula

Show that the equation x - 2x + 4x - 1 = 0 can be rearranged to give the iterative formula:

x =

3

2

1 - 4x

x - 2

n+1

n

n

Rearranging to give an iterative formula

Show that the equation x - 2x + 4x - 1 = 0 can be rearranged to give the iterative formula:

x =

3

2

1 - 4x

x - 2

n+1

n

n

x - 2x = 1 - 4x

x (x - 2) = 1 - 4x

x = x =

1 - 4x

x - 2

2

1 - 4x

x - 2

2

2

3

Activity

Complete the jigsaw to match the equation to the correct iterative formulae.

Activity

Complete the jigsaw to match the equation to the correct iterative formulae.

**Activity**

Answers

Answers

**Activities**

**Key**

Examples

Examples

**Worked**

Example

Example

**Worked**

Example

Example